Volume incompliance and transfusion are essential for transfusion‐associated circulatory overload: a novel animal model - Klanderman, Robert B. (Transfusion, 2019)
BACKGROUND: Transfusion‐associated circulatory overload (TACO) is the predominant complication of transfusion resulting in death. The pathophysiology is poorly understood, but inability to manage volume is associated with TACO, and observational data suggest it is different from simple cardiac overload due to fluids. We developed a two‐hit TACO animal model to assess the role of volume incompliance (“first‐hit”) and studied whether volume overload (“second‐hit”) by red blood cell (RBC) transfusion is different compared to fluids (Ringer's lactate [RL]). MATERIALS AND METHODS: Male adult Lewis rats were stratified into a control group (no intervention) or a first hit: either myocardial infarction (MI) or acute kidney injury (AKI). Animals were randomized to a second hit of either RBC transfusion or an equal volume of RL. A clinically relevant difference was defined as an increase in left ventricular end‐diastolic pressure (ΔLVEDP) of +4.0 mm Hg between the RBC and RL groups. RESULTS: In control animals (without first hit) LVEDP was not different between infusion groups (Δ + 1.6 mm Hg). LVEDP increased significantly more after RBCs compared to RL in animals with MI (Δ7.4 mm Hg) and AKI (Δ + 5.4 mm Hg), respectively. Volume‐incompliant rats matched clinical TACO criteria in 92% of transfused versus 25% of RL‐infused animals, with a greater increase in heart rate and significantly higher blood pressure. CONCLUSION: To our knowledge, this is the first animal model for TACO, showing that a combination of volume incompliance and transfusion is essential for development of circulatory overload. This model allows for further testing of mechanistic factors as well as therapeutic approaches.